PENGARUH SOSIAL MASYARAKAT TERHADAP MINAT MENABUNG DI BANK SYARIAH INDONESIA (Studi Pada Masyarakat Desa Sido Mulyo Kecamatan Tungkal Jaya) - Novi Yuni Putri; Efni Anita; G.W.I. Awal Habibah (Lembaga Pengembangan Kinerja Dosen, 2023)
At this time, as we know, there is low public interest in saving at Bank Syariah Indonesia, where based on preliminary observations, it shows that most people still save their own money and do not fully trust Bank Syariah Indonesia. It is hoped that sharia banking can form socialization associations in religious activities so that they can understand better so that they are in accordance with Islamic teachings towards sharia banking so that they can attract the attention of the people of Sido Mulyo Village to Indonesian sharia banks, so that they become good and more concrete behavior. This study aims to determine whether there is social influence on the interest in saving at Bank Syariah Indonesia. This study uses a quantitative method by obtaining primary data from a questionnaire by taking as many as 100 respondents using a non-probability sampling technique, namely purposive sampling by choosing people who have never saved at Bank Syariah Indonesia. Simple regression analysis is used as a data analysis technique. The results of this study indicate that social community has a positive and significant effect on the intention to save at Bank Syariah Indonesia. Based on data analysis in this study, these variables are valid and reliable. In testing the classical assumption with a normal distribution, heteroscedasticity does not occur. The results of the positive regression coefficient mean that the direction of the relationship is unidirectional, the magnitude of the effect is 5.7% and the rest is influenced by other variables